2020
DOI: 10.3389/fphys.2020.578866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10 vs. 20-Min Injury Prevention Program on Neuromuscular and Functional Performance in Adolescent Football Players

Abstract: Background: Regular injury prevention training is not only effective in reducing sports injury rates, but also in improving neuromuscular and performance-related variables. However, it is currently unknown if this effect can be modified by varying the training dosage. Objective: To compare the effects of two injury prevention programmes with a different training duration on neuromuscular control and functional performance in adolescent football players. Methods: 342 (15.4 ± 1.7 years) male football players fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Since football is one of the leading sports worldwide, research that focuses on this issue exists, but the results of practical implementation in youth football remains limited [28]. Rahlf et al proved that performing structured neuromuscular training with a longer duration ( > 20 minutes) pre-training is effective for improving lower extremity flexibility in in adolescent football players [29]. Van der Horst et al reported that incorporating the Nordic hamstring exercise (NHE) protocol in regular training significantly reduces hamstring injury incidence in amateur football players in a randomized controlled trial [30].…”
Section: Discussionmentioning
confidence: 99%
“…Since football is one of the leading sports worldwide, research that focuses on this issue exists, but the results of practical implementation in youth football remains limited [28]. Rahlf et al proved that performing structured neuromuscular training with a longer duration ( > 20 minutes) pre-training is effective for improving lower extremity flexibility in in adolescent football players [29]. Van der Horst et al reported that incorporating the Nordic hamstring exercise (NHE) protocol in regular training significantly reduces hamstring injury incidence in amateur football players in a randomized controlled trial [30].…”
Section: Discussionmentioning
confidence: 99%
“…To account for possible dropouts, 42 participants were included. Effect size calculation was based on data of own studies using the WBLT and Y-Balance test (John et al, 2019 ; Rahlf et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It remains to be investigated if high-quality and high-intensity NHE execution will result in more reliable data, higher compliance, and greater neuromuscular adaptations—especially at longer muscle lengths—compared to traditional high-volume interventions [ 2 , 7 , 8 , 19 , 64 , 81 ]. Progression of exercise volume with increasing strength level, as suggested by the FIFA 11+ program [ 15 , 33 , 92 , 96 , 120 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ], might not be the method of choice for purposeful injury prevention [ 94 ]. Furthermore, the implementation of single- or multiple-set NHE regimen as part of the warm-up should be reconsidered and should instead be performed during the cool-down routine [ 42 , 56 , 58 , 81 , 135 ].…”
Section: Discussionmentioning
confidence: 99%